Comprehensive approach to diabetic nephropathy - Bancha Satirapoj; Sharon G. Adler (Kidney Research and Clinical Practice, 2014)
Diabetic nephropathy (DN) is a leading cause of mortality and morbidity in patients with diabetes. This complication reflects a complex pathophysiology, whereby various genetic and environmental factors determine susceptibility and progression to end-stage renal disease. DN should be considered in patients with type 1 diabetes for at least 10 years who have microalbuminuria and diabetic retinopathy, as well as in patients with type 1 or type 2 diabetes with macroalbuminuria in whom other causes for proteinuria are absent. DN may also present as a falling estimated glomerular filtration rate with albuminuria as a minor presenting feature, especially in patients taking renin–angiotensin–aldosterone system inhibitors (RAASi). The pathological characteristic features of disease are three major lesions: diffuse mesangial expansion, diffuse thickened glomerular basement membrane, and hyalinosis of arterioles. Functionally, however, the pathophysiology is reflected in dysfunction of the mesangium, the glomerular capillary wall, the tubulointerstitium, and the vasculature. For all diabetic patients, a comprehensive approach to management including glycemic and hypertensive control with RAASi combined with lipid control, dietary salt restriction, lowering of protein intake, increased physical activity, weight reduction, and smoking cessation can reduce the rate of progression of nephropathy and minimize the risk for cardiovascular events. This review focuses on the latest published data dealing with the mechanisms, diagnosis, and current treatment of DN.